Are High-Heat-Producing Granites Essential to the Origin of Giant Lead-Zinc Deposits at Mount Isa and McArthur River, Australia? (1992 Canadian Institute of Mining, Metallurgy and Petroleum) - M. Solomon (Canadian Institute of Mining, Metallurgy and Petroleum, 1992)
Giant, sediment-hosted lead-zinc deposits in northern Australia fonned during development of Mid-Proterozoic extensional basins that overlie Lower Proterozoic basement. The basement in the Mount Isa area, exposed by folding and faulting, contains fractionated, high-heat-producing granites. These granites generate heat at a rate of about 6",Wm-3, probably sufficient to fonn giant lead-zinc deposits either by (a) driving episodic convection of saline basement and basin fluids for periods of IOS to 106 years at temperatures of about 230°C, or (b) heating basin fluids moving under the influence of topographic relief or fault movement. The presence or absence of such granites may form a vital component of the genetic model. Ore-fonning fluid flow was probably initiated by continent-scale, extensional basin fracturing.